2019
DOI: 10.3390/w11112344
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment by Constructed Wetland Eco-Technology: Influence of Mineral and Plastic Materials as Filter Media and Tropical Ornamental Plants

Abstract: Constructed wetlands (CWs) are sustainable technologies where the channels are filled with porous material and plants, which collectively remove pollutants, depending on the type of substrate and vegetation. This study evaluated CWs and their functionality by comparing three ornamental plants (Canna indica, Cyperus papyrus, and Hedychium coronarium) as a phytoremediation process of wastewater, in CWs filled with layers of porous stone–tepezil–plastic residues–soil (S-A), or in microcosms with layers of porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…For example, the purification efficiencies of CWs designed with ornamental plants is 93.8% for TN, 80.0% for dissolved organic carbon (DOC), 84.0% for the biochemical oxygen demand (BOD 5 ), 77.0% for the chemical oxygen demand (COD), and 99.7% for the turbidity, which not only effectively remove nutrients and improve the wastewater quality, but the cannas also bring certain landscape benefits [155]. In addition, Sergio Zamora et al used three ornamental plants (Canna indica, Cyperus papyrus, and Hedychium coronarium) as a phytoremediation process for wastewater, and they found that all three plants were able to remove more pollutants than the experimental setup without plants, which confirms that ornamental vegetation can be used in CW systems [156]. Immediately after, LC Sandoval-Herazo et al investigated the ability of ornamental plants to remove pollutants at different densities, and they showed that high-density planting facilitated the removal of 10% to 20% of the pollutants [157].…”
Section: Additional Benefits Of Cws For Water Managementmentioning
confidence: 95%
“…For example, the purification efficiencies of CWs designed with ornamental plants is 93.8% for TN, 80.0% for dissolved organic carbon (DOC), 84.0% for the biochemical oxygen demand (BOD 5 ), 77.0% for the chemical oxygen demand (COD), and 99.7% for the turbidity, which not only effectively remove nutrients and improve the wastewater quality, but the cannas also bring certain landscape benefits [155]. In addition, Sergio Zamora et al used three ornamental plants (Canna indica, Cyperus papyrus, and Hedychium coronarium) as a phytoremediation process for wastewater, and they found that all three plants were able to remove more pollutants than the experimental setup without plants, which confirms that ornamental vegetation can be used in CW systems [156]. Immediately after, LC Sandoval-Herazo et al investigated the ability of ornamental plants to remove pollutants at different densities, and they showed that high-density planting facilitated the removal of 10% to 20% of the pollutants [157].…”
Section: Additional Benefits Of Cws For Water Managementmentioning
confidence: 95%
“…In addition to reducing emissions of pollutants at the source, it is also necessary to intercept pollutants in the transmission pathway and carry out ecological restoration of agricultural ecosystem [ 55 , 56 ]. Some ecological engineering techniques like ecological ditches, constructed wetlands, and vegetated filter strips should be applied in Xuzhou section [ 57 , 58 ]. Secondly, measures are needed to control the release of phosphorus from sediments to water.…”
Section: Resultsmentioning
confidence: 99%
“…They observed in their experiments about 70% of reduction in total suspended solids (TSS) and biochemical oxygen demand (BOD), 50% to 60% of reduction in nitrogen, ammonia, and phosphate levels, and a significant reduction in feacal coliform populations. Whereas, Zamora et al (2019) found the removal efficiency of chemical oxygen demand (COD), total solids suspended (TSS), nitrogen as ammonium (N-NH 4 ) and nitrate (N-NO 3 ), and phosphate (P-PO 4 ) up to…”
Section: Wastewater Treatment By Using Plant Speciesmentioning
confidence: 99%